The influence of regional taxes and regional retributions on regional original income in the Aceh provincial government - Ritonga, Mirwansyah Putra (Institute of Computer Science (IOCS), 2024)
This research aims to examine the influence of regional taxes and regional levies on Local Original Income during the 2012-2014 budget year. The research object is regional taxes and regional levies. The research method used is qualitative research using multiple linear regression equations processed with SPSS version 21. The data source used is primary data, namely the financial reports of the Aceh Provincial Government for 2012-2014. The research results show that there is a simultaneous influence of regional taxes and regional levies on the Aceh Provincial Government's Local Original Income revenue in 2012-2014. Partially, regional taxes have a positive effect on the Local Original Income of the Aceh Provincial Government, where every increase in the realization of regional tax revenues also increases the Local Original Income. Meanwhile, regional levies have a negative effect on Local Original Income of the Aceh Provincial Government. The magnitude of the influence of regional taxes and regional levies on Local Original Income of the Aceh Provincial Government is 23.8%, while the remaining 76.2% is influenced by other variables not included in this research, such as balancing funds, regional spending, and so on.